Nilai-Nilai Budaya Jawa Dalam Ungkapan Jawa yang Berlatar Rumah Tangga Pada Novel Canting Karya Fissilmi Hamida - Sri Suharti (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2021)
Abstract A harmonious household is the dream for every people. A lot of efforts can be done to build a harmonious household. One of the way for building the harmonious household, is by setting a certain value system as the basis of a household. That value system could be sourced from legal, religion, social, and culture. There is no doubt that Javanese culture is the source of the values basis for a household. These values could be expressed by an oral tradition form called Javanese expressions. Javanese expressions are a expression form of Javanese ideas through the beautiful and high valuable words which containing the moral values. That value could be as a life guidance for peoples and community in various purposes, including in household life as a life after married. This study reveals Javanese cultural values in Javanese expressions within a household life background in the novel entitled Canting by Fissilmi Hamida. This study conducted by a sociology of literature approach with descriptive analysis method. The results of this study found that there are five Javanese cultural values contained in Javanese expressions within a household background in the novel entitled Canting by Fissilmi Hamida, namely belief value (firmness), patience value, achievement value (hopes and goals), and harmony value. Abstrak Rumah tangga harmonis adalah dambaan setiap orang. Banyak upaya yang dapat dilakukan untuk menciptakan rumah tangga harmonis. Salah satunya dengan menjadikan sistem nilai tertentu sebagai landasan berumah tangga. Sistem nilai tersebut bisa bersumber dari hukum, agama, sosial, maupun budaya. Budaya Jawa sebagai sumber tata nilai  sebagai landasan berumah tangga tidak diragukan lagi keberadaannya.  Tata nillai tersebut dituangkan dalam bentuk tradisi lisan yang disebut dengan ungkapan Jawa. Ungkapan Jawa merupakan bentuk ekspresi ide gagasan Jawa melalui kata-kata yang bernilai indah dan tinggi  dan mengandung nilai-nilai moral yang dapat dijadikan sebagai pedoman hidup bagi masyarakat dalam beraneka tujuan, termasuk dalam menjalani  berumah tangga.  Penelitian ini mengungkap nilai-nilai budaya Jawa dalam ungkapan-ungkapan Jawa berlatar rumah tangga dalam novel Canting karya Fissilmi Hamida. Penelitian ini menggunakan pendekatan sosiologi sastra dengan metode analisis deskriptif.  Hasil penelitian menunjukkan ada lima nilai budaya Jawa yang terdapat dalam ungkapan-ungkapan Jawa berlatar rumah tangga dalam novel karya Fissilmi Hamida yaitu nilai keyakinan (keteguhan), nilai kesabaran, nilai pencapaian (harapan dan cita-cita), nilai keselarasan.